The Household Consumption In Algeria, Behavioral Transition Towards Expenditure After 2000 - حمداوي , هجيرة; دلندا , عيسى (مجلة المقدمة للدراسات الانسانية و الاجتماعية, 2022)
The North African countries have, since their independence, known great economic and social upheavals. These changes constitute a privileged observation platform for food policy analysts. Studies by agronomists, epidemiologists, sociologists and economists have shown that food consumption habits and patterns are a precise mirror and well reflecting the socio-economic level of a population. Important socio-economic changes have affected the population’s choices towards consumption and nutrition with consequences for the resurgence of non-communicable diseases and obesity the daily ratio of the Algerian citizen which is determined by his social, economic and cultural level, should be revisited and redirected to his benefit for the long term. Other factors such as health, lifestyle, activity etc. Can be taken into consideration, but as a major determinant, the economic factor plays a fundamental role in the consumption of the citizen and in his classification based on his priorities.